2020
DOI: 10.1002/cctc.202001371
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Applying Carbonyl‐stabilized Phosphorus Ylides for Catalysis

Abstract: The exploration of new catalytic properties of the known functionalities would facilitate the exploitation of new ligands and/or organocatalysts that are able to achieve reactivity and selectivity unattainable by known ones. In this context, carbonyl‐stabilized phosphorus ylides have emerged as a type of novel ligand motifs and organocatalysts, exhibiting versatile catalytic activity towards some important organic reactions such as cross‐couplings, cyanation, CO2 fixation. This Minireview summarizes these rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 91 publications
0
5
0
Order By: Relevance
“…For sterically hindered meta-and ortho-methoxyphenyl bromides, reduced product yields of 54% and 28%, respectively, were obtained (entries 12 and 13). Expanding beyond styrene, the catalyst system proved highly efficient with n-butyl acrylate as the alkene partner (entries [14][15][16][17][18]. For examples, quantitative yields of coupled products were achieved in 6 h when 4-chlorobenzonitrile and 4-chloroacetophenone were used (entries 14 and 15).…”
Section: Paper Dalton Transactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For sterically hindered meta-and ortho-methoxyphenyl bromides, reduced product yields of 54% and 28%, respectively, were obtained (entries 12 and 13). Expanding beyond styrene, the catalyst system proved highly efficient with n-butyl acrylate as the alkene partner (entries [14][15][16][17][18]. For examples, quantitative yields of coupled products were achieved in 6 h when 4-chlorobenzonitrile and 4-chloroacetophenone were used (entries 14 and 15).…”
Section: Paper Dalton Transactionsmentioning
confidence: 99%
“…Transition metal complexes involving phosphonium ylides have been attracting interest over several decades. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Recently, Gessner et al introduced a pioneering class of palladium complexes featuring ylide-functionalized phosphine ligands known as YPhos (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the intriguing catalytic properties of chiral (salen)AlCl and (salen)TiCl 2 complexes activated by a suitable phosphorane ligand in asymmetric cyanation reactions, we hope the understanding of the structure of such phosphorane-salen metal complexes will be helpful for developing chiral or achiral phosphorous ylide ligands derived chiral metal complexes for asymmetric catalysis, which is a field in its infancy. 69 On the other hand, the Lewis basic additive HMPA is also used to improve the stereoselectivity. NMR analysis revealed that the interaction of HMPA and Me 2 (CH 2 Cl)SiCN (2) might produce a bulky nucleophilic species, HMPA(SiMe 2 CH 2 Cl)(N=C:), similar to Corey's proposal that binding of TMSCN by Ph 3 PO led a more reactive isocyanide species Ph 3 P(OTMS)(N=C:).…”
Section: Mechanistic Studiesmentioning
confidence: 99%
“… The strong σ-donating and weak π-accepting abilities of NHC ligands often impart enhanced catalytic activity and improved stability in many transition metal complexes, particularly Pd and Ni complexes that are widely used in catalytic organic cross-coupling reactions. Like NHCs, organic ylides, most notably phosphorus ylides (P-ylides), comprise an alternative family of Lewis basic carbon donor (C-donor) ligands capable of coordinating a wide range of main group and transition metal centers ( 2 , Scheme ). Moreover, experimental evidence indicating that phosphorus ylides are stronger C-donor ligands than many NHCs has been reported. , Notably, however, utilization of P-ylide metal complexes in homogeneous catalysis has received scant attention. In addition, other types of C-donor ligands for catalytically relevant transition metals have not been extensively developed.…”
Section: Introductionmentioning
confidence: 99%